Prevalence and risk factors associated with severe pre-eclampsia among postpartum women in Zanzibar: a cross-sectional study - Mwashamba M. Machano; Angelina A. Joho (BMC, 2020)
Abstract Background Severe pre-eclampsia is more dominant in low and middle-income countries. In Sub-Saharan Africa, severe pre-eclampsia remains a major public health problem contributing to high rates of maternal mortality. Few studies have investigated the relationship between severe pre-eclampsia and associated factors in East Africa. The aim of this study was to determine the prevalence and risk factors associated with severe pre-eclampsia among postpartum women in Zanzibar. Methods A hospital based analytical cross-sectional study design was used. Purposive sampling was utilized for the selection of hospitals. Proportionate sampling was used for selection of representatives from each hospital and participants were selected using systematic random sampling. Postpartum mothers were included in the study. The study was conducted by an interviewer who administered a questionnaire with close ended questions and chart review for data gathering. SPSS version 23 was used for data analysis and descriptive and multiple logistic regression was performed for control of confounders. Results This study included a total of 400 participants with a 100% response rate. Participants ranged from 17 to 45 years of age with mean age (SD) of 28.78 (±6.296). The prevalence of severe pre-eclampsia among postpartum women was 26.3% (n = 105). After adjusting for the possible confounders, factors associated with severe pre-eclampsia were; maternal age group of 15-20 years (AOR 3.839; 95% C. I 1.037-14.210), pregnancy from new partner/husband (AOR 7.561; 95% C. I 3.883-14.724), family history of high blood pressure (AOR 6.446; C. I 3.217-12.917), diabetes prior to conception (AOR 55.827; 95% C. I 5.061-615.868), having high blood pressure in a previous pregnancy (AOR 19.382; 95% C. I 4.617-81.364), paternal age above 45 (AOR 2.401; 95% C. I 1.044-5.519) and multifetal gestation (AOR 7.62; 95% CI 2.01-28.84). Conclusion The prevalence of severe pre-eclampsia among postpartum women in Zanzibar is high. Common risk factors in this setting include maternal age of 15-20 years, pregnancy with a new partner, family history of high blood pressure, pre-existing diabetes prior to conception, a history of high blood pressure in previous pregnancy paternal age greater than 45 and multifetal gestation.